Mednarodna pristojnost v sporih glede premoženjskih razmerij med zakoncema - Pogorelčnik Vogrinc, Neža (Podjetje in delo, 2020)
Council Regulation (EU) 2016/1103 of 24 June 2016 implementing enhanced cooperation in the area of jurisdiction, applicable law and the recognition and enforcement of decisions in matters of matrimonial property regimes determines unified rules regarding international jurisdiction for matrimonial property disputes, which are used instead of international private law of the 18 member states participating in the enhanced cooperation. Primarily, the international jurisdiction for disputes of this kind applies to two kinds of procedures in progress. Where a court of a member state is seized in matters of the succession of a spouse or to rule on an application for divorce, legal separation or marriage annulment, the courts of that state shall have jurisdiction to rule on matters of the matrimonial property regime arising in connection with that case. Because the need to decide on matrimonial property regime arises mostly in the events of the death of one of the spouses or the end of the marriage, the provisions on concentration of the procedures are to be used often. The connecting factors to determine the international jurisdiction, as provided in Regulation 2016/1103, are therefore rarely used. Because of the sensitivity of the field and different levels of development of societies in member states, the unification of regulation gives rise to many questions. The article stresses the consequences of the usage of Regulation 2016/1103 instead of the Slovenian Private International Law and Procedure Act, and interprets instruments, helping to determine the international jurisdiction when it is not possible to use general rules.
Keywords: choice of court agreement; connecting factors; dogovor; international jurisdiction; marriage; mednarodna pristojnost; navezne okoliščine; premoženjska razmerja; Private International Law and Procedure Act; property regimes; Regulation 2016/1103; Uredba 2016/1103; Zakon o zakonski zvezi in družinskih razmerjih; zakonska zveza